Formation of research competence of students in the process of studying the syntax of the Ukrainian language - Derkach, Larysa Mykolaivna; Vitiuk, Valentyna VolodymyrIivna; Sukalenko, Tetiana Mykolaivna; Marchuk, Liudmyla Mykolaivna; Lebed, Iuliia Borysivna (AD ALTA: Journal of Interdisciplinary Research, 2021)
The article deals with the specifics of the formation of research competence of higher education students in studying the syntax of the Ukrainian language as an important approach to training future teachers of philology, which integrates the intellectual potential of the student, his creative activity, cognitive motivation. Various theoretical approaches to the study of the research approach in language teaching are analyzed. Emphasis is placed on the main components of language research competence: independent search, research, problem solving; creative experience related to the production of new ideas, language patterns; ability to apply the acquired knowledge of the Ukrainian language in research activities; language knowledge as an element of the content of education and the result of assimilation of theoretical information. It was found that the basis of the research type of teaching Ukrainian syntax is a problem-solving method aimed at self-development of personality, and an important aspect of the formation of research competence of future teachers of Ukrainian language and literature while studying syntax is the creation of problems related to independent search explanation, substantiation, proof of connections between linguistic concepts and phenomena, formulation of own conclusions. The most productive types of problem tasks during the study of the syntax of the Ukrainian language are determined: aimed at the study of certain syntactic units; search problems; tasks with research elements; educational and cognitive tasks. Examples to each type of the specified tasks with the explanation of expediency of their application at studying of different subjects from syntax are shown.
Keywords: language research competence; problem task; research approach; research competence; syntax